O herói, seu antagonista e sua ideologia em três filmes de super-herói - Nunes, El Buainin Vieira Machado (2019)
This thesis seeks to analyze the heroes and its related antagonists of the films The Amazing Spider Man (2012), Man of Steel (2013) and Deadpool (2016). The main question is: what is the ideology that these characters promote? Considering the Motion Picture Association of America (MPAA), which is the state institution of the United States (USA), regulatory agency of the production of these films, the theoretical framework with which the research studies these characters consists mainly of the concepts of cultural industry (ADORNO; HORKHEIMER, 1985), of movie industry (BENJAMIN, 2012), of discourse and ideology (MARX; ENGELS, 2001; EAGLETON, 2003), of cultural industry of American imperialism de (IANNI, 1976), of mastery over the minds (ROMANO, 15 nov. 2016), of Pax Americana (SOARES, 2015) and of messages and propaganda (COMBS; COMBS, 1994). The reading of these productions is made from excerpts of the screenplay and their visual context. These characters are allegoric and they represent dichotomously the good and the Evil, as I could see in this investigation. The Good is associated to what the USA, as a State, represents, since its army until the lifestyle that it intends to promote. The Evil is associated to any discourse that stands in opposite to its good, to a greater or lesser extent. I chose these films because they were the most successful among the ones that tell the story of the origin of a hero up to 2016, when this study started. That is to say, billions of people around the world saw these films and the impact that this phenomena can cause might not be calculated. In identifying themselves with the main characters, who always have a tragedy in their fictitious family life, audience tends to choose “the Good side”; that is, they tend to choose the American ideological version of the world, submitting themselves to the Pax Americana and to its mastery of the minds